PENGARUH PRODUK, HARGA, TEMPAT,DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PADA M-SEE MART NATAR - Cici Salsabela; Selfia Alke Mega (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The rapid expansion of the retail sector, particularly minimarkets in Indonesia, has intensified business competition. This situation requires retailers to implement appropriate marketing strategies to attract consumers and enhance purchase intention. M-See Mart Natar is a local minimarket that offers various daily necessities; however, it continues to experience a low level of customer visits. This condition highlights the need to examine marketing factors that influence consumer purchase intention.This study aims to assess the impact of product, price, location, and promotion on consumer purchase intention at M-See Mart Natar. Methods: Using a survey procedure, a quantitative research approach was implemented. 91 respondents who had previously shopped at M-See Mart Natar were requested to complete questionnaires. A purposive sampling technique was implemented. The validity, reliability, and classical assumption tests were conducted after the data were analyzed using multiple linear regression analysis with the assistance of SPSS software.Result: The results suggest that consumer purchase intention is, in part, positively and significantly influenced by product, price, and promotion. At the same time, location does not exhibit a substantial impact. Concurrently, consumer purchase intention is substantially influenced by product, price, place, and promotion. The results of this study are anticipated to offer M-See Mart management valuable insights for the enhancement of marketing strategies to pique consumer interest in purchasing. Keywords:  Product, Price, Place, Promotion, Purchase Intention